Women Victimization on Islamic State of Iraq and Syria (ISIS): A Critical Analysis On Terrorist Wives - Leebarty Taskarina, Leebarty Taskarina (Jurnal Keamanan Nasional, 2020)
Nowadays, perpetrators on terrorism are not male dominated. Research in this thesis discusses women's involvement as terrorist wives to support their husband and their terrorist groups. This research focused on the process of how wives were brought and involved in terrorism by their husband. Terrorist wives are the invisible victim of terrorism, they are involved not by their own will. Pressure, intimidation, dominance and symbolic violence in their household move toward a new kind of victimization. Using a qualitative approach in-depth interview with two terrorist wives, this research found terrorist wives experienced multiple victimizations. Another finding is also made that wives are unconscious that they are actually victims with society's unawareness showing that there is an omission by the government. Terrorist wives not only experience multiple impacts, but also they are neglected victims of counter-terrorism systems.